2014
DOI: 10.3892/or.2014.3422
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of PMA-induced tumor cell invasion and migration by ginsenoside Rg1 via the inhibition of NF-κB-dependent MMP-9 expression

Abstract: Ginseng has become one of the most commonly used alternative herbal medicines, and its active component, ginsenoside Rg1 has known pharmacological effects, including anticancer properties. However, the effects of ginsenoside Rg1 on metastasis have yet to be investigated. In this study, we demonstrated the ability of ginsenoside Rg1 to suppress phorbol myristate acetate (PMA)-induced invasion and migration in MCF-7 breast cancer cells. MCF-7 cells were treated with ginsenoside Rg1 and incubated with or without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 25 publications
(20 reference statements)
2
41
0
Order By: Relevance
“…Our previous study showed that a P. notoginseng ethanol extract inhibited HCT-116 cell migration by significantly decreasing MMP-9 but had no effect on MMP-2 expression (9). Ginsenoside Rg1 also suppressed PMA-induced MMP-9 expression but did not affect MMP-2 expression (38). In the present study, NGR1 was found to regulate MMP-9 expression in the HCT-116 cells.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Our previous study showed that a P. notoginseng ethanol extract inhibited HCT-116 cell migration by significantly decreasing MMP-9 but had no effect on MMP-2 expression (9). Ginsenoside Rg1 also suppressed PMA-induced MMP-9 expression but did not affect MMP-2 expression (38). In the present study, NGR1 was found to regulate MMP-9 expression in the HCT-116 cells.…”
Section: Discussionsupporting
confidence: 48%
“…Ginsenoside Rg1 also suppressed transforming growth factor β1 (TGF β1)-induced invasion and migration in HepG2 liver cancer cells (36). In addition, by inhibiting MMP-13 expression, ginsenoside Rg3 significantly suppressed the migration, invasion, wound healing, and colony-forming abilities of B16F10 cells in a dose-dependent manner (37), and by inhibiting wound healing and MMP-9 expression via suppression of NF-κB phosphorylation and DNA binding activity, ginsenoside Rg1 suppressed phorbol myristate acetate-induced invasion and migration in MCF-7 breast cancer cells (38). The above studies indicate that saponins can reduce the activities of MMPs to inhibit cancer metastasis.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, AAA is defined as a chronic inflammatory condition with a proteolytic imbalance. Ginsenosides have exhibited potential biological functions in AAA suppression, e.g., inhibition of MMP expression and attenuation of the inflammatory response [36][37][38]. However, no direct effect of ginsenosides on AAA development has been reported.…”
Section: Discussionmentioning
confidence: 98%
“…33,34 Exosomes from MCF7 cells or MCF7 cells treated with PMA to increase their malignant potential failed to display thrombotic activity with fibrinogen or human platelet-poor plasma (supplemental Figure 1B). However, thrombotic activity was detected with MVs from MCF7 cells with fibrinogen or human platelet-poor plasma (supplemental Figure 1A), whereas MVs from PMA-treated MCF7 cells displayed thrombotic activity only in the presence of fibrinogen (supplemental Figure 1A).…”
Section: Thrombotic Activity Of Exosomes and Mvsmentioning
confidence: 99%